Guidance and counseling interventions for bullying prevention in adolescents - Zikry Latupasjana; Firman Firman; Riska Ahmad (Indonesian Institute for Counseling, Education and Theraphy, 2023)
Adult bullying problems are increasingly prevalent in Indonesia. Bullying that often occurs in schools disrupts students from achieving optimal development. This is important to be addressed immediately so that bullying does not develop in schools. Guidance and counseling is a unit that is able to help in alleviating this problem. This research uses a literature study approach regarding the impact and ways of dealing with bullying in Minangkabau youth. Bullying refers to a form of bullying or violence that is intentionally carried out by one person or group of people who are stronger or more powerful against another person, with the aim of hurting and is carried out continuously. The development of technology, makes it easier for people to do bullying, not only occurs directly, but also occurs on social media. Guidance and counseling is one of the units in the school that is considered capable of preventing bullying behavior with various services.